Radon exposure and potential health effects other than lung cancer: a systematic review and meta-analysis - Henyoh, Afi Mawulawoe Sylvie; Laurent, Olivier; Mandin, Corinne; Clero, Enora (Frontiers in Public Health, 2024)
Context and objective: To date, lung cancer is the only well-established health effect associated with radon exposure in humans. To summarize available evidence on other potential health effects of radon exposure, we performed a comprehensive qualitative and quantitative synthesis of the available literature on radon exposure and health effects other than lung cancer, in both occupational and general populations. Method: Eligible studies published from January 1990 to March 2023, in English and French languages, were identified in PubMed, ScienceDirect, Scopus, ScieLo and HAL. In the meta-analysis, we estimated average weighted standardized incidence ratios (metaSIR), standardized mortality ratios (metaSMR), and (metaRR) per 100 unit (Bq/m 3 or Walking level Month) increase in radon exposure concentration by combining estimates from the eligible studies using the random-effect inverse variance method. DerSimonian & Laird estimator was used to estimate the between-study variance. For each health outcome, analyses were performed separately for mine workers, children, and adults in the general population. Results: A total of 129 studies were included in the systematic review and 40 distinct studies in the meta-analysis. For most of these health outcomes, the results of the meta-analyses showed no statistically significant association, and heterogeneity was only present among occupational studies, especially between those included in the metaSIR or metaSMR analyses. However, the estimated exposure-risk associations were positive and close to the statistical significance threshold for: lymphohematological cancer incidence in children (metaRR = 1.01 ; 95%CI: 1.00 -1.03 ; p = 0.08); malignant melanoma mortality among adults in the general population (metaRR = 1.10 ; 95%CI: 0.99 -1.21 ; p = 0.07); liver cancer mortality among mine workers (metaRR = 1.04 ; 95%CI: 1.00 -1.10 ; p = 0.06); intestine and rectal cancer mortality combined among mine workers (metaRR = 1.02 ; 95%CI: 1.00 -1.04 ; p = 0.06). Conclusion: Although none of the exposure-risk associations estimated in the meta-analyses reached statistical significance, the hypothesis that radon may have other health effects apart from lung cancer.